The role and practical importance of digital educational technologies in the organization of drawing lessons (Zien Journal of Social Sciences and Humanities, 2023)
This article describes in detail the role and practical importance of digital educational technologies in the organization of drawing classes, the important requirements for the organization of modern educational technologies in drawing classes.